Etnobotani Tumbuhan Liar yang Dimanfaatkan sebagai Obat oleh Masyarakat Suku Mandailing di Kecamatan Lubuk Barumun Kabupaten Padang Lawas - Ratimah Daulay; M. Idris (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to document wild plants used as medicinal resources by the Mandailing ethnic community in Lubuk Barumun District, Padang Lawas Regency, and to identify plant diversity, processing methods, utilized plant organs, and phytochemical contents of the most frequently used species. The research employed a descriptive method, with data collected through open interviews involving 20 respondents and field observations, followed by qualitative phytochemical screening of three dominant species. The results revealed 20 plant species belonging to 13 families used in traditional medicine. Leaves were the most commonly utilized plant organ, while pounding and boiling were the primary preparation methods. Phytochemical screening indicated that Ageratum conyzoides L., Acalypha indica L., and Stachytarpheta jamaicensis (L.) Vahl contain flavonoids, saponins, tannins, and steroids, with alkaloids detected in Stachytarpheta jamaicensis. In conclusion, the traditional healing practices of the Mandailing community are supported by the presence of potentially pharmacologically active secondary metabolites and reflect sustainable utilization of biological resources; however, further quantitative and pharmacological studies are required to strengthen scientific validation.   Keywords: Ethnobotany, Phytochemistry, Mandailing Community, Traditional Knowledge, Medicinal Plants